Health burdens related to emission sources and cross-provincial air pollution in China - Weiyang Hu; Bo Zheng; Daven K. Henze; Ni Lu; Xiaolin Wang; Lin Zhang; Tzung-May Fu; Yu Zhao (npj Climate and Atmospheric Science)
Abstract Effective abatement of air-pollution-induced health damages requires a comprehensive understanding of the changing roles of individual sources and cross-regional transport. Here, we estimate premature mortality attributable to specific source categories, precursor species, and regions within mainland China. We find that the marginal national premature deaths, dominated by PM2.5 exposure, have declined from 151,842 per 10% growth of emissions in 2013 to 111,271 in 2020, and would further to 54,293 in 2035 following a carbon peaking and carbon neutrality pathway. The impacts of certain species-category combinations have grown including NOX from industrial combustion and off-road traffic. The proportions of cross-provincial to marginal health burden have remained stable at around 50%. Provinces with net exporting of premature deaths were intensively located in the north of China while those with net importing were in the south. Our findings highlight the need for a location-precursor/sector-specific strategy of emission controls in China’s public health regulatory framework.